i-Tasmi' Tahfiz: innovation for memorizing Al-Quran / Noorimah Misnan ... [et al.] - Misnan, Noorimah; Salleh, Wan Anisabanum; Abdul Manaf, Suhaily Maizan; Mohamad, Mohammad Taqiuddin (Academy of Contemporary Islamic Studies (ACIS), 2021)
The word 'Tahfiz' has been derived from the lexical item 'Hafaz', conjugated as a past-tense verb, which means "strongly memorized and was able to recite (Quranic verses, etc.) by heart without having to refer to books, references, and others". Meanwhile, Tasmi' refers to a method in which a student recites his or her newly memorized verses to a Quranic teacher until he or she could be able to spot and correct the student's errors/mistakes in his or her Quranic recitation. In Malaysia, Tahfiz schools have played a great role in spreading Tahfiz al-Quran education. Tahfiz-Integrated Curriculum was introduced in 2014 in several religious schools. Tahfiz certification was offered by the Ministry of Education at both primary and secondary levels. However, as Tahfiz students continued their studies at university levels, the methodology of Tahfiz education has begun to take a rear seat. An innovative technique of i-Tasmi' Tahfiz is a drill-and-practise method used by students for memorizing Quranic verses and chapters. Previous studies have found that there is a correlation between students' academic and behavioural excellences and the teaching and learning methods used in Tahfiz education. The objective of this research is to enlighten the impact of the model of i-Tasmi' Tahfiz towards the teaching and learning process of university students. A pilot study has documented the implementation of the i-Tasmi' Tahfiz model at UiTM Terengganu Branch by using both quantitative and qualitative approaches. The respondents in this study were 18 students and the results show that the students who are involved in Tasmi' al-Quran classes are inclined to retaining their subjects much more effortlessly, shaping their charismatic characters more efficiently, and obtaining flying-colour results academically. These demonstrate that the application of i-Tasmi' Tahfiz is applicable to university students as it helps them to elevate their academic and extra co-curricular performances and enables them to graduate on time (GOT). The innovative i-Tasmi' Tahfiz Apps has been developed and it is hoped that it can be registered for intellectual property protection.